Occurrence of Toxoplasma gondii in raw goat, sheep, and camel milk in Upper Egypt - Saad, Nagah M. (Vet World, 2018)
BACKGROUND AND AIM: Toxoplasmosis is a worldwide zoonotic disease with harmful effects on animal and human health. Ingestion of contaminated raw milk has been suggested as a vehicle for transmission of Toxoplasma gondii to human. The present study was performed for the detection of T. gondii in raw milk samples of goat, sheep, and camel in Upper Egypt using two different techniques (enzyme-linked immunosorbent assay [ELISA] and quantitative polymerase chain reaction [qPCR]). MATERIALS AND METHODS: This study was conducted to determine the T. gondii prevalence using ELISA and qPCR in raw goat, sheep, and camels milk (30 samples for each) collected from different locations in Upper Egypt. RESULTS: T. gondii IgG antibodies were detected in 90.0, 60.0, and 3.33% of goat, sheep, and camel milk samples, respectively. From the positive samples of T. gondii IgG, the parasitic DNA was detected only in two examined milk samples, one of them was present in goat milk sample and another one was found in sheep milk sample. On the other hand, the parasite was not detected in camels’ milk samples. CONCLUSION: These results concluded that the raw milk was contaminated by T. gondii tachyzoites which could be a source of human infection. Restricted hygienic programs should be implemented in the animal farms to decrease the risk of milk contamination by this parasite.